2019
DOI: 10.3390/nu11092034
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Interdependencies of Human Milk Macronutrients, Fatty Acids, Adiponectin, Insulin, and IGF-II in the European PreventCD Cohort

Abstract: Human milk composition is variable. The identification of influencing factors and interdependencies of components may help to understand the physiology of lactation. In this study, we analyzed linear trends in human milk composition over time, the variation across different European countries and the influence of maternal celiac disease. Within a multicenter European study exploring potential prevention of celiac disease in a high-risk population (PreventCD), 569 human milk samples were donated by women from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 70 publications
4
10
0
1
Order By: Relevance
“…An Australian study [ 46 ] including 20 breastfeeding dyads showed that casein concentration in HM and calculated daily intakes of casein in infants were positively associated with lower infant fat-free mass ( p = 0.003, n = 18), higher fat mass ( p < 0.001), fat mass index ( p = 0.001, n = 18), and % fat mass ( p < 0.001, n = 18) measured with ultrasound skinfolds. Grunewald et al [ 47 ] confirmed these results. They studied 196 pairs of mothers and infants from a European research project (PreventCD) and found that one-month milk protein content was strongly associated with infant serum lyso-phosphatidylcholine (LPC) 14:0 (linear mixed effect model corrected for multiple testing— P LME = 0.009).…”
Section: Discussionmentioning
confidence: 62%
“…An Australian study [ 46 ] including 20 breastfeeding dyads showed that casein concentration in HM and calculated daily intakes of casein in infants were positively associated with lower infant fat-free mass ( p = 0.003, n = 18), higher fat mass ( p < 0.001), fat mass index ( p = 0.001, n = 18), and % fat mass ( p < 0.001, n = 18) measured with ultrasound skinfolds. Grunewald et al [ 47 ] confirmed these results. They studied 196 pairs of mothers and infants from a European research project (PreventCD) and found that one-month milk protein content was strongly associated with infant serum lyso-phosphatidylcholine (LPC) 14:0 (linear mixed effect model corrected for multiple testing— P LME = 0.009).…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, milk sampling for analysis (9 months after birth) could have been completed at an earlier point, given that infants' gut microbiota modulation by breastfeeding also starts earlier. However, this analysis could only be done at 9 months because: earlier samples were processed for macronutrient and endocrine profiling (Grunewald et al, 2019), all available milk sample from mothers included in this pilot study were uniform at this time point, and because all were still breastfeeding their children, together with the introduction of complementary food. Accordingly, we assumed that hMM would still act as a modulator of the infants' gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other biological fluids, many bioactives in milk show considerable sensitivity to sampling methodology and analytical technique (Demmelmair & Koletzko, 2017; Grunewald et al, 2019; Mehta & Petrova, 2014) analysis. Collection time and sample volume can introduce significant variation into milk samples and may bias results (Miller et al, 2013).…”
Section: Influence Of Methodology On Human Milk Composition: the Impomentioning
confidence: 99%